COVID-19 and the impact on the education of healthcare professionals across countries with a particular focus on developing countries (Bangladesh Journal of Medical Science, 2022)
Abstract not availableBangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 221-232